Simulation of Robot Navigation for Hospital’s Confined Space Areas Using Fuzzy Control - Razak, A.A.A.; Abdullah, A.H.; Kamarudin, K.; Saad, F.S.A.; Shukor, S.A.A.; Mustafa, H.; Bakar, M.A.A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The atmospheric hazards that may be present in confined space pose a serious threat to human while carrying special task in the respective location. Among the areas that are considered as confined space are utility tunnel, boiler, storage tank, sewage lines, utility holes and underground electrical fault. This study is concerned with hospital’s enclosed space areas which include mechanical room and medicine storage area. Currently, there is no specific technique to replace worker for a task such as navigation and collecting air sample in the confined space for monitoring the hazards. A mobile robot integrated with CCD camera can be used to manoeuvre through the environment and at the same time monitor the situation in confined space. This paper discusses simulation of robot navigation for hospital’s confined space areas. Fuzzy control was implemented to allow the robot to perform semiautonomous obstacle avoidance in the simulated environment. The result shows that the robot was able to manoeuvre around without any collision.